Fertility Preservation in Girls - Jennia Michaeli; Michael Weintraub; Eitan Gross; Yehuda Ginosar; Vardit Ravitsky; Einat Eizenman; Eduardo Mitrani; Meital Lebovich; Neri Laufer; Stephen Kennedy; Ariel Revel (Hindawi Limited, 2012)
Children that undergo treatment for cancer are at risk of suffering from subfertility or hormonal dysfunction due to the detrimental effects of radiotherapy and chemotherapeutic agents on the gonads. Cryopreservation of ovarian tissue prior to treatment offers the possibility of restoring gonadal function after resumption of therapy. Effective counseling and management of pediatric patients is crucial for preserving their future reproductive potential. The purpose of this article is to review recent literature and to revise recommendations we made in a 2007 article. Pediatric hemato-oncology, reproductive endocrinology, surgery, anesthesia and bioethics perspectives are discussed and integrated to propose guidelines for offering ovarian cryopreservation to premenarcheal girls with cancer.